1999
DOI: 10.1177/002076409904500406
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Relationships and Quality of Life: Association of Two Subjective Constructs in Schizophrenia Patients

Abstract: Subjective quality of life is an important criterion in outcome evaluation that has been well-researched in psychiatry. By comparison, the therapeutic relationship which may also be subjectively assessed has been relatively neglected as an outcome criterion although it has predictive power in relation to outcome. This exploratory study investigated subjective quality of life and therapeutic relationships in first-admission (N = 90) and long-term (N = 168) schizophrenia patients, each at two points of time. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…Precaution must be taken when comparing this study with previous ones; illness duration is not well defined, and samples vary between outpatients, inpatients and patients in residential facilities. Development of a therapeutic relationship with treating staff increases QOL in inpatients with long-term illness (McCabe, Rӧder-Wanner, Hoffmann, & Priebe, 1999). Also, adaptation to changing conditions might alter the patient's goals, expectations, standards and concerns, thereby increasing QOL (Oort, Visser, & Sprangers, 2009).…”
Section: Illness Durationmentioning
confidence: 99%
“…Precaution must be taken when comparing this study with previous ones; illness duration is not well defined, and samples vary between outpatients, inpatients and patients in residential facilities. Development of a therapeutic relationship with treating staff increases QOL in inpatients with long-term illness (McCabe, Rӧder-Wanner, Hoffmann, & Priebe, 1999). Also, adaptation to changing conditions might alter the patient's goals, expectations, standards and concerns, thereby increasing QOL (Oort, Visser, & Sprangers, 2009).…”
Section: Illness Durationmentioning
confidence: 99%
“…However, there are findings from different psychiatric settings, showing that the therapeutic alliance correlates with outcome (4)(5)(6)(7)(8). The therapeutic alliance is also associated with a better outcome in pharmacotherapy (9,10), with adherence to medication and treatment recommendations (11)(12)(13) and with patients' perceptions of quality of life (14). The therapeutic relationship also seems significant for the outcome in other than traditional psychiatric settings, such as in general practitioners' treatment of psychological problems (15) and in counselling (16).…”
Section: Introductionmentioning
confidence: 99%
“…Perceptions of coercion in service provision could potentially influence satisfaction in all aspects of an individual's life. McCabe et al (1999) found a significant relationship between quality of life and therapeutic relationships in long-term psychiatric patients, but no significant relationship was found in first-admission patients. McCabe et al suggested that ''therapeutic relationships may become more central to quality of life in long-term care situations and patients' views of this relationship are increasingly embedded in their overall appraisal of life'' (p. 280).…”
Section: Introductionmentioning
confidence: 72%